Tijauan Mekanisme Koping dan Strategi Pertahanan Diri Siswa Korban Perundungan di Lingkungan Sekolah - Putri Hidayati; Chairunnisa Chairunnisa; Ahmaddin Ahmad Tohar (AL - IBRAH, 2025)
This study aims to examine the phenomenon of bullying in schools from an educational psychology perspective using the library research method. This study reviews various scientific sources, such as journals, books, and research reports, to understand the forms, causes, characteristics of perpetrators and victims, impacts, and strategies for preventing bullying in educational settings. The results of the study show that bullying includes physical, verbal, social, and cyber forms that are repetitive and accompanied by an imbalance of power. The contributing factors include individual aspects, such as low empathy and self-control, as well as environmental factors, such as parenting patterns and school culture. Perpetrators generally exhibit dominant and aggressive traits, while victims tend to be passive and have low self-esteem. The impacts include psychological distress, decreased academic performance, and the risk of antisocial behavior. Effective strategies to address bullying include a whole-school approach, character education, and social-emotional learning. This study emphasizes that bullying is not only an individual behavioral problem but also a reflection of the weakness of the education system in creating a safe and empathetic learning environment.